Evaluation of customer service in a traditional candy museum. - Torres González, Amada; Sánchez Flores, Verónica; Aguilar Olivé, Claudia Gabriela (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2026)
OBJECTIVE: To analyze the perception of  quality service at the 'Museo del Dulce' (Candy Museum) located in the municipality of Jalapa, Tabasco, Mexico, in order to identify improvement areas that contribute to a better visitor experience.​MATERIAL AND METHOD: This is a quantitative study with a descriptive scope, cross-sectional, and non-experimental. A survey was applied which included the variables of empathy, information of quality, responsiveness, communication, tangible elements, and satisfaction. The questionnaire consists on 25 items answered on a Likert-type scale ranging from "totally disagree" to "totally agree". 52 visitors, who were approached on-site, participated voluntarily.​RESULTS: They showed a favorable perception regarding the evaluated factors; however, areas of opportunity for improvement were also identified. Among them are the need for continuous staff training, implementing suggestion boxes to receive feedback, improving the quality of information in the provided brochures, and incorporating new technologies.​CONCLUSIONS: Users suggest to be offered tastings samples of candies and regional products, which will help to improve the experience.
Keywords: museum; service; traditional candy.